The relationship between high gravity brewing, key performance indicators and yeast osmotic stress response - Zhuang, S. (2014)
High Gravity (HG) and Very High Gravity (VHG) fermentations are increasingly attractive within the brewing industry as a means of energy-saving and to optimise process efficiency. However, the use of highly concentrated worts is concomitant with a number of biological stress factors and in particular elevated osmotic pressure, which can impact on yeast quality and fermentation performance. In order to eliminate or reduce such negative effects, yeast cells often respond to their environment by adapting their central carbon metabolism and by making osmotic adjustments. The aim of this research was to investigate the impact of wort gravity on carbon flux, key performance indicators and to examine the effect of external osmolality (as a measure of osmotic pressure) on cell physiology. The fermentation performance of lager and ale brewing yeasts in standard (13 °P), HG (18 °P) and VHG (24 °P) worts was assessed with respect to the uptake of wort sugars, and the production of key carbon metabolites. Estimation of carbon partitioning revealed that products including trehalose, glycogen, higher alcohols and esters had only minor effects on carbon distribution, whereas the production of yeast biomass acted as a major trade-off with ethanol production. Moreover, parallel analysis of the fermentation environment indicated that osmolality increased during fermentations, particularly at high gravities, with the largest contribution directly related to ethanol production. Consequently, yeast cells were subjected to a series of increasing osmolality levels induced by sorbitol, designed to replicate high gravity conditions. These conditions were shown to have a negative impact on yeast viability and vitality, although cell genome integrity was unaffected. In addition, cells responded to osmotic pressure by modifying membrane components leading to a change in fluidity, and by promoting glycerol production. It is anticipated that the data presented here will provide a greater understanding of the response of yeast to HG and VHG conditions, potentially leading to process optimisation in the future.